Is there a Role for Cortisol in the Accumulation of Lipids in the Intima a Crucial Step of Atherogenesis? - Fantidis, Panayotis; Eladio, Sanchez; Ibrahim, Tarhini; Tomas, Pineda; Jose Antonio, Corrales; Jose Ramon, Gonzalez (Current Vascular Pharmacology, 2015)
Accumulation of lipids in the intima is the initial and crucial step in atherogenesis, but, this step is not always synonymous with atherogenesis. The factors that trigger the mechanisms modulating lipid accumulation in the vessel wall and in the subsequent development of atherosclerotic plaque remain unclear. In this review we evaluate whether atherogenesis is modulated by cortisol, the end hormone of the stress-related anti-inflammatory system. The amount of accumulated lipids in the intima depends on the balance between the penetration and efflux of cholesterol from the artery wall. We assess whether cortisol is involved in this balance. Cortisol can increase the penetration of lipids, and, simultaneously, might reduce their efflux from the intima. We also report a critical analysis on whether atherogenesis, which has a local nature, can be modulated by a systemic factor. In addition, we comment on the synergistic action of cortisol with insulin in atherogenesis, and consider relevant recent clinical evidence regarding the role of cortisol in atherosclerosis. Glucocorticoids, by triggering the mechanisms that favor the penetration of lipids in the intima, and modulating factors that control the efflux of cholesterol from the artery wall, may lead to the formation of atherosclerotic plaques. Thus, cortisol may have a role in atherogenesis. This may have important clinical, therapeutic and preventive implications.
Keywords: Atherogenesis